Hegel's political philosophy: on the normative significance of method and system - Stein, Sebastian; Brooks, Thom (Oxford University Press, 2017)
This ground-breaking collection of new essays by leading interpreters of Hegel's philosophy is dedicated to the questions that surround Hegel's philosophical method and its relationship to the conclusions of his political thought
Includes bibliographical references and index
This edition previously issued in print: 2017
Zielgruppe - Audience: Specialized
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Politische Philosophie; Hegel, Georg Wilhelm Friedrich